(3GdJMaI GdTGgjI aj cTa GdCSQGQ GdadcjIs - (3GdaGQSj, GdTjQGRj, bWH GdOjf, eMehO Hf eSYhO Hf eUdM, J (B710 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3dhdG Cf GdYGOI ShZJ ddCUGZQ GdGfHSGW Edi GdCcGHQ dGSJLeYJ GdGYJUGe HYQGge hGdGSJYGfI HbhGge Ydjge hGdeHGgGI HGdGJUGd Hge hGdeHGQI aj GdGJcGd Ydjge (B...s
(3BNQgG (B:s
... (3Ef GfVGa Edi GdChd chf GdbeQ SQjYG hGdTeS HWjFI hZjQ Pdc ef GdCSHGH hGdi GdKGfj (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B7/187s
(3cTa GdXfhf (B1/367s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdadc hGdJfLje hGdejbGJs